2015
DOI: 10.4172/2375-446x.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofield Treated Energized Water on the Growth and Health Status in Chicken (Gallus gallus domesticus)

Abstract: The current study was attempted to investigate the effect of Mr. Trivedi's biofield energy treated energized water on chicken. The total 4200 chicks were equally divided into two groups i.e. control and treated. The biofield treated energized water was provided to the treated chicks, while the control chicks were drunk with standard drinking water. During the experiment the parameters such as mortality, body weight, food intake etc. were assessed in both control and energized water treated birds. The mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The proton and carbon signals for CH, CH 2 and CO groups in the proton and carbon NMR spectra were observed almost similar for the control and the treated samples. The percentage change in the isotopic abundance ratio of P M+1 /P M ( 2 H/ 1 H or 13 C/ 12 C or 17 O/ 16 O or 25 Mg/ 24 Mg) was significantly decreased in the treated sample by 17.51% compared with the control sample. Consequently, the isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 26 Mg/ 24 Mg) in the treated sample was significantly increased by 79.44% compared to the control sample.…”
Section: ® -Biofield Energy Healing Treatment Remotely By Twenty Renomentioning
confidence: 83%
See 1 more Smart Citation
“…The proton and carbon signals for CH, CH 2 and CO groups in the proton and carbon NMR spectra were observed almost similar for the control and the treated samples. The percentage change in the isotopic abundance ratio of P M+1 /P M ( 2 H/ 1 H or 13 C/ 12 C or 17 O/ 16 O or 25 Mg/ 24 Mg) was significantly decreased in the treated sample by 17.51% compared with the control sample. Consequently, the isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 26 Mg/ 24 Mg) in the treated sample was significantly increased by 79.44% compared to the control sample.…”
Section: ® -Biofield Energy Healing Treatment Remotely By Twenty Renomentioning
confidence: 83%
“…Consequently, the isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 26 Mg/ 24 Mg) in the treated sample was significantly increased by 79.44% compared to the control sample. Briefly, 13 C, 2 H, 17 O, and 25 Mg contributions from (C 12 H 23 MgO 14 ) + to m/z 416; 18 O and 26 Mg contributions from (C 12 H 23 MgO 14 ) + to m/z 417 in treated sample were significantly altered compared with the control sample. Thus, The Trivedi Effect ® Treated magnesium gluconate might be supportive to design the novel potent enzyme inhibitors using its kinetic isotope effects.…”
Section: ® -Biofield Energy Healing Treatment Remotely By Twenty Renomentioning
confidence: 99%
“…This process is known as The Trivedi Effect ® -Energy of Consciousness Healing Treatment [17,18] [19]. Biofield Energy Treatment (The Trivedi Effect ® ) has been drawn attention more in the recent times for its scientifically measurable capability to transform the characteristic properties of a wide varieties living and nonliving substances such as plants [20,21], animals [22], microbes [23,24], cancer cells [25], medium [26,27], materials [28,29], pharmaceuticals [30,31], nutraceuticals [32,33], organic compounds [34,35]. The scientific study indicated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternate method for increasing or decreasing the natural isotopic abundance ratio of the substances [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [17] [18]. Biofield Energy Treatment (The Trivedi Effect ® ) has been drawn attention more in the recent times for its scientifically measurable capability to transform the characteristic properties of a wide varieties living and nonliving substances such as animals [19], cancer cells [20], microbes [21,22], plants [23,24], medium [25,26], materials [27,28], pharmaceuticals [29,30], nutraceuticals [31,32], organic compounds [33][34][35]. The scientific study indicated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternate method for increasing or decreasing the natural isotopic abundance ratio of the substances [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%